2021
DOI: 10.1007/s40243-021-00195-9
|View full text |Cite
|
Sign up to set email alerts
|

Stability, reusability, and equivalent circuit of TiO2/treated metakaolinite-based dye-sensitized solar cell: effect of illumination intensity on Voc and Isc values

Abstract: In this research, treated metakaolinite (TMK) was introduced into the TiO2 photoelectrode to fabricated dye-sensitized solar cells (DSSCs). The photovoltaic cells have four main natural components, i.e., a photosensitizer (carotenoid bixin), photoelectrode (TiO2/kaolinite), electrolyte (glycerine carbonate derivative), and counter-electrode (carbon). Their stability, reusability, and equivalent circuit were studied. The presence of 5% of TMK in anatase TiO2 paste decreased the TiO2 band gap from 3.21 to 3.16 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…This feature gives a more stable chemical bond and permits excellent interconnection and continuity between titania nanoparticles, which in turn enhances electron transfer efficiency in photoanode [18]. This phenomenon showed that the inclusion of SnO2 in the TiO2 may stabilize the anatase as the main and strongest phase.…”
Section: Resultsmentioning
confidence: 91%
“…This feature gives a more stable chemical bond and permits excellent interconnection and continuity between titania nanoparticles, which in turn enhances electron transfer efficiency in photoanode [18]. This phenomenon showed that the inclusion of SnO2 in the TiO2 may stabilize the anatase as the main and strongest phase.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, incorporating bixin into the interlayer space of kaolinite can increase the stability of bixin. The stability of kaolinite-bixin organoclay increased up to 15% compared to pure bixin [8]. Another study has reported that when used as a sensitizer, the Znbixin complex can be stable up to 700 W m -2 irradiation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of DSSC reusability can be done by irradiating solar cells for several days until the cells are completely dead or unable to produce current. Rahmalia et al [8] reported that TiO2/treated metakaolinite-based DSSC could survive for up to 3 days with a rest period of 17 hours after being exposed to light continuously for 7 hours under an intensity of 200 Wm -2 .…”
Section: Introductionmentioning
confidence: 99%
“…Bixin has been shown to reduce the inflammatory response and atherosclerotic plaque in hypercholesterolemic rabbits [4] and prevent neuroinflammation and demyelination in mice [5]. Rahmalia et al [6][7] used bixin as a sensitizer, such as a light filter, so it has the potency to protect food products from oxidation due to light.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1), as well as carotenoids, several researchers have reported increased stability in many ways, such as impregnation, encapsulation, complexation, and incorporation of bixin or norbixin molecules into other materials [8][9][10][11][12][13]. Our previous research has successfully synthesized the metal- bixin complex through the reflux method using conventional organic solvent [7]. This method can improve the polarity and photostability of bixin, as well as prevent clouding or loss of color from bixin, which is generally caused by the encapsulation method [12].…”
Section: ■ Introductionmentioning
confidence: 99%